A new species of amphipod of the genus Demaorchestia Lowry & Myers, 2022 (Senticaudata, Talitridae) from Chilika Lagoon, east coast of India - Bhoi, Gitanjali; Tarafdar, Lipika; Patro, Shesdev (Zootaxa, 2023)
The genus Demaorchestia Lowry & Myers, 2022 comprises five species globally. This paper adds a new species D. alanensis sp. nov. to this group, thus increasing the total number of global species to six. The sample was collected from the shoreline of Chilika Lagoon near Barkul, east coast of India. The new species can be distinguished from the other members of the genus by having two or three groups of robust setae on the anterior margin of the propodus of gnathopod 1. With the description of this new species, the article further confirms the occurrence of the subfamily Platorchestiinae and the genus Demaorchestia along Indian coast.